Flow‐cytometric minimal residual disease monitoring in blood predicts relapse risk in pediatric B‐cell precursor acute lymphoblastic leukemia in trial AIEOP‐BFM‐ALL 2000. Issue 5 (18th December 2018) - Schumich, Angela; Maurer‐Granofszky, Margarita; Attarbaschi, Andishe; Pötschger, Ulrike; Buldini, Barbara; Gaipa, Giuseppe; Karawajew, Leonid; Printz, Dieter; Ratei, Richard; Conter, Valentino; Schrappe, Martin; Mann, Georg; et al.
Abstract: Background: Flow‐cytometric monitoring of minimal residual disease (MRD) in bone marrow (BM) during induction of pediatric patients with acute lymphoblastic leukemia (ALL) is widely used for outcome prognostication and treatment stratification. Utilizing peripheral blood (PB) instead of BM might be favorable, but data on its usefulness are scarce. Procedure: We investigated 1303 PB samples (days 0, 8, 15, 33, and 52) and 285 BMs (day 15) from 288 pediatric ALL patients treated in trial AIEOP‐BFM ALL 2000. MRD was assessed by four‐color flow cytometry and evaluated as relative, absolute, and kinetic result. Results: In B‐ALL only, PB measures from early time points correlated with relapse incidence (CIR). Best separation occurred at threshold <1 blast/μL at day 8 (5‐year CIR 0.02 ± 0.02 vs 0.12 ± 0.03; P  = 0.044). Patients with highest relapse risk were not distinguishable, but PB‐MRD at days 33 and 52 correlated with prednisone response and postinduction BM‐MRD by PCR ( P  < 0.001). Kinetic assessment did not convey any advantage. In multivariate analysis including day 15 BM‐MRD, PB‐MRD measures lost statistical power. Conclusions: In summary, PB‐MRD in pediatric B‐ALL correlates with outcome and risk parameters, but its prognostic significance is not strong enough to substitute for BM assessment in AIEOP‐BFM trials. It might, however, be valuable in treatment environments not using multifaceted risk stratification with other MRD measures.